Retardation mechanism of cement hydration by a comb polyphosphate superplasticizer. (17th October 2022) - Mezhov, Alexander; Ben Shir, Ira; Schmidt, Asher; Kovler, Konstantin; Diesendruck, Charles E.
Graphical abstract: Schematic presentation of the interaction between model cement and directly added polycarboxylate and polyphosphate superplasticizers. Highlights: At low doses, polyphosphate SP inhibits silicate reaction without affecting aluminate reaction and formation of ettringite. At high doses, polyphosphate SP retards silicate and aluminate reactions, which follows by acceleration of both reactions. Polyphosphate SP has higher affinity to C3 S compared to PCE. Retardation induced by direct addition of polyphosphate SP is similar to retardation induced by delayed addition of PCE. Abstract: The retardation mechanism of cement hydration as imparted by the addition of polyphosphate comb superplasticizer to model cement containing C3 S, C3 A and calcium sulfate hemihydrate is studied using XRD, ss NMR and calorimetry. Our findings show the retardation effect caused by the direct addition of polyphosphate comb superplasticizer differs significantly to that of conventional polycarboxylate superplasticizers. Conversely to polycarboxylates, polyphosphates, at a low dosage, inhibits the silicate reaction without affecting the aluminate reaction and formation of ettringite. Yet, at high doses, both reactions are hampered, and the induction period extended, followed by accelerated aluminate and silicate reactions.